Multiple insecticide resistance in the major malaria vector Anopheles funestus in southern Ghana: implications for malaria control. Issue 1 (December 2016) - Riveron, Jacob; Osae, Michael; Egyir-Yawson, Alexander; Irving, Helen; Ibrahim, Sulaiman; Wondji, Charles
Abstract Background Understanding the dynamics of insecticide resistance in African malaria vectors is crucial for successful implementation of resistance management strategies in the continent. This study reports a high and multiple insecticide resistance inAnopheles funestus from southern Ghana which could compromise the Malaria Operational Plan in this country, if not tackled. AdultAnopheles mosquitoes were collected in Obuasi and Adawukwa, in southern Ghana.Plasmodium infection rates, susceptibility to the main insecticides used in public health and the molecular basis of insecticide resistance were established. Results An. funestus (sensu stricto ) (s.s .) was the predominant mosquito species found resting inside the houses in Obuasi, while at Adawukwa it was found together withAn. coluzzii . Parasite rates were high inAn. funestus (s.s .) populations from both localities, withPlasmodium infection rates greater than 12.5 %. Both, An. funestus (s.s .) andAn. coluzzii, from the two sites exhibited high resistance to the insecticide from various classes including the pyrethroids, carbamates and DDT, but remained fully susceptible to the organophosphates. A preliminary characterization of the underlying molecular mechanisms of resistance inAn. funestus (s.s .) populations from both sites revealed thatCYP6P9a, CYP6P9b, CYP6M7 andGSTe2 genes are upregulated, markedly higher in Obuasi (between 3.35 and 1.83 times) than in Adawukwa population. The frequency of L119F-GSTe2 and A296S-RDL resistance markers were also higher in Obuasi (42.5 and 68.95 % higher), compared withAn. funestus (s.s .) populations from Adawukwa. These findings suggest that the similar resistance pattern observed in bothAn. funestus (s.s .) populations are driven by different mechanisms. Conclusions Resistance to multiple insecticides in public health use is present in malaria vectors from Ghana with major resistance genes already operating in the field. This should be taken into consideration in the design of resistance management strategies to avoid operational failure.